Orthodontic-surgical treatment of four impacted canines in an adult patient: A case report - Pavlovic, Jasna A; Tabaković, Saša Z; Simić, Sanja; Vujačić, Amila; Vukićević, Vladanka (Vojnosanitetski pregled, 2017)
Introduction.Full impaction of canines, in both jaws, is a rare phenomenon. It is usually coupled with the persistence of deciduous canines, or any other irregularity in the dental arch. Case report. Panoramic radiograph of a 24-year-old female patient showed bilateral canine impaction in both jaws. Due to vestibular, apical and medial position of canines in the upper jaw, the surgical approach implied the apically positioned flap technique. The position of impacted mandibular canines was vertical with more coronal position relative to the upper canines, thus requiring a closed eruption technique. Conclusion. Inadequate position of impacted canines in the bone fully justifies the use of orthodontic-surgical treatment.
Keywords: tooth; impacted; radiography; dental; digital; oral surgical procedures; orthodontics; treatment outcome